Realisasi Kesahihan Estetika Dalam Karya Sastra Arab - Novita Rahmi (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2019)
Aesthetics that studies beauty will decrease in value if it is associated with sensual or worldly pleasures. Conversely, if aesthetics are associated with morals and religion, the value will be even higher. We can find this aesthetic value in works of art such as Arabic literary. Arabic literary that contain the essence of beauty are prose or poetry that is able to invite the reader to draw closer to Allah SWT and His Rasul, giving rise to religious zeal and social solidarity, such as aesthetics understood by Sufis: Imam Ghazali, Harith bin Thabit, Rabiah Al Adawiyyah, Al Jufri, Faris bin Isa al Baghdadi, Umayyah ibn Abi Shult. They are able to create Arabic literary that are rich in aesthetic validity.